Menelaah Problem Teologis Dialog antar-Agama - Muttaqin, Muttaqin Muttaqin; Jamal, Jamal Jamal; Kusuma, Amir Reza; rahmadi, alif rahmadi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Issue between religious believers is an interesting issue to be discussed. The issue comes to conflict when there is a truth claim in every religion. So that religious leaders assume that inter-faith dialogue is the solution of the conflict. There are two dialogue models offered which are; sosilogical realm, that endless to harmony and peace and theological realm, wanting to reconcile the doctrine or concepts of God in every religion as solution of the problems. But the solution which is offered can cause serious problematic in the form of believing religious teachings. This paper aims to reveal the secret mission of inter-faith dialogue, which is to deconstruct aqidah or faith. To achieve this goal, the paper research used theological and philosophical approaches, for knowing the subtle mode of dialogue offered by Christian teologians or other scientists. This research uses a descriptive analysis method to analyze dialogue methods in the theological sphere with the muslim scientists perspective to know how the dialogue should be in Islamic teachings. The study resulted in several conclusions. First, in the inter-faith dialogue there is a subtle effort to leveler the concept of God from every religion in the esoteric region or its inner. Second, inter-faith dialogue is a vehicle to disseminate of the global teology. Third, in dialogue there is a subtle effort of christianization.